Preparation and magnetic properties of manganese silicide nanorods by a solid‐state reaction route. (1st March 2018) - Lu, Juanjuan; Wang, Liangbiao; Zhang, Junhao; Li, Qianwen; Liu, Weiqiao; Lou, Zhengsong; Zheng, Ao; Zhou, Quanfa
Abstract : Manganese silicide (Mn5 Si3 ) nanorods were successfully prepared using manganese sesquioxide (Mn2 O3 ), silicon (Si) and metallic magnesium (Mg) as starting materials via a solid‐state route in an autoclave. X‐ray powder diffraction pattern revealed that the obtained product was hexagonal phase Mn5 Si3 . Furthermore, the oxidation resistance and magnetic properties of the obtained Mn5 Si3 nanorods were also investigated.